The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/978-3-642-02713-0_19
|View full text |Cite
|
Sign up to set email alerts
|

“Where Did I Put That?” – Effectiveness of Kinesthetic Memory in Immersive Virtual Environments

Abstract: Kinesthetic memory is an essential factor in human interaction with the outside world. It helps adept keyboard users to type rapidly and hit the keys without having to look at them. It enables musicians to play their instruments without consciously having to think about the necessary movements. And it can help people to find things again, based on the location where they put them. The benefits of kinesthetic memory in the physical world are well known and well used for training or in physical therapy. Yet litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…More recent research on spatial and content memory completely removed user input from the study and focused solely on the effect of visual grids [15]. Ebert et al explored the combination of spatial and kinesthetic memory in front of a wall-sized 3D vision display with real depth perception [6]. Users performed a memory task in a 3D scene with mouse vs. physical navigation, i.e., walking in front of the screen.…”
Section: )mentioning
confidence: 99%
“…More recent research on spatial and content memory completely removed user input from the study and focused solely on the effect of visual grids [15]. Ebert et al explored the combination of spatial and kinesthetic memory in front of a wall-sized 3D vision display with real depth perception [6]. Users performed a memory task in a 3D scene with mouse vs. physical navigation, i.e., walking in front of the screen.…”
Section: )mentioning
confidence: 99%
“…Kinesthetic memory refers to the extent that the human body can recall its movements and postures. Through the use of sensory-motor learning and development of kinesthetic memory, a person can accomplish specific physical movements without thinking about how his or her body's parts should move (Ebert, Deller, Steffen, & Heintz, 2009). Interviews with 16 professional welders and welding engineers revealed that they felt that sensory-motor learning was a very important component of successful welding.…”
Section: Introduction Motivationmentioning
confidence: 99%
“…Moreover, at least two other additional criteria for measuring the improved abilities of the trainees were proposed in literature of VR/MR studies for training. The first one is the measurement of trainees' ability to recall the acquired skills and actions for a correct performance, such as, the economy of movements, and the accuracy of posture and actions measured in terms of time and accuracy within the training sessions [33,43,62,63]. The second criterion is the skill-decay [64][65][66][67].…”
Section: Performance Criteriamentioning
confidence: 99%